THE INFLUENCE OF SCIENCE AND IPS DEPARTMENT ON LEARNING OUTCOMES IN CLASS XI STUDENTS IN CITIZENSHIP EDUCATION. - Noviah, Ema; Tjalla, Awaluddin; Mahdiyah, Mahdiyah (International Journal of Business, Law, and Education, 2023)
In this study, the factors causing differences in students’ abilities were focused on the intelligence factor used by the school to place students in the Science and Social Studies specialization group. This difference in placement was based on cognitive ability, and student interest carried out by the school. Schools still consider the division of the second major to be more critical based on moderate to low levels of cognitive abilities, so students are in the social studies class group, while moderate to high cognitive abilities are in the science class group. Citizenship education subjects are divided into two groups, where the groups have been divided based on students’ cognitive abilities. In this group condition, the two social studies and science class groups should have a different impact on student learning outcomes. Is the justification that the Social Studies class group, which is grouped based on medium to low cognitive abilities, has lower student end-of-semester exam results than the Science class group, or is it the other way around? This research is included in the quasi-experimental research with a purposive sampling technique. This research was conducted on class XII high school students majoring in science and social studies. Data collection techniques for learning outcomes use good descriptions to measure knowledge or skills. The data analysis technique used is non-parametric (Mann-Whitney U Test). The results of the research show that the learning outcomes of students majoring in civic education in social studies are lower than those majoring in natural sciences, or the learning outcomes of students majoring in natural sciences are higher in citizenship education than students majoring in social studies.